Diamond p-FETs using two-dimensional hole gas for high frequency and high voltage complementary circuits. (2nd February 2023) - Kawarada, Hiroshi
Abstract: Diamond is a wide bandgap semiconductor (bandgap: 5.5 eV). However, through impurity doping, diamond can become a p-type or n-type semiconductor. The minimum resistivity of p-type semiconductor diamond is less than 10 −3 Ω cm, which is no more than that of silicon (Si). In contrast, the minimum resistivity of n-type diamond is as high as 10 3 Ω cm. At present, the development of unipolar devices such as p-channel field-effect transistors (p-FETs) based on diamond is strongly anticipated. When the diamond surface is terminated using hydrogen (H) or Si atoms, the subsurface layer becomes a p-type accumulation layer or inversion layer that forms a two-dimensional hole gas (2DHG), which can then be used as a channel for a FET structure. As a p-FET, the performance of this device approaches that of other wide bandgap semiconductor n-channel FETs. One of the main advantages of this diamond p-FET is that the p-type accumulation or inversion layer is formed natively on the hydrogen terminated (C–H) diamond. This review describes the low metal contact resistance that induces 2DHG formation on the C–H diamond surface, on which negatively charged sites are formed. The negatively charged surface model explains the 2DHG formation clearly based on the FET's operating mechanism. Recent advances in 2DHG FETs are also discussed, particularly in terms of their current densities of >1 A mm −1 and their high frequency performance. Finally, we propose two types of complementary high-voltage circuit that combine diamond p-FETs with other wide bandgap semiconductor n-FETs.